Moderasi Beragama Mahasiswa Kota Bandung: Aktualisasi dalam Hubungan Sesama Muslim dan Antaragama - Hernawati, Hernawati; Ibrohim, Iim; Supala, Supala (Fakultas Agama Islam Universitas Muhammadiyah Bandung, 2024)
The urgency of this research is to observe the moral decadence among the younger generation. Morality, known as ahlak in Islam, is very important in life because ahlak is above knowledge. One form of ahlak reflection is the actualization of religious moderation. This is crucial considering the multicultural condition in Indonesia. This research aims to understand the actualization of religious moderation among students in Bandung City. The research uses a quantitative approach with a survey research method. Data collection is done using questionnaires distributed to students in several universities in Bandung City. Respondents are asked to fill out surveys related to the actualization of religious moderation which exhibited in their daily lives. Religious moderation is measured in terms of moderation in relationships among fellow Muslims and moderation in interfaith relationships. The research data is analyzed using the SPSS tool. The research findings show that aspects of religious moderation in most indicators of relations with fellow Muslims are in the high to very high category, with some indicators reaching very high values, indicating a strong understanding and application of religious moderation in relations with fellow Muslims among the respondents. The overall average value of these indicators is 3.2, which means it is in the very high category. The average value of aspects of actualization of religious moderation in interfaith relationships is 2.77, showing a high level of religious moderation, especially in terms of mutual respect and participation in social activities together, although support and solidarity still have room for improvement. Keywords: religious moderation; students; interfaith relationships; solidarity